2015
DOI: 10.1002/agr.21421
|View full text |Cite
|
Sign up to set email alerts
|

Price Transmission in the European Tomatoes and Cauliflowers Sectors

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 42 publications
1
24
0
4
Order By: Relevance
“…Their results are in line with numerous studies [40,42,46] and in contrast with the results presented by Kim and Ward [59]. In addition, Santeramo [7] concludes that, in markets of perishable products, price rises tend to be slowly transmitted and do not influence distant markets; on the contrary, shocks originated by price decreases spread across markets. The results are in line with Ward [40] who has demonstrated that the high perishability, and the inability to delay sales through temporary storage implies that decreases in wholesale prices have a larger effect on retail prices than increases.…”
Section: A Focus On Perishable Marketssupporting
confidence: 86%
See 1 more Smart Citation
“…Their results are in line with numerous studies [40,42,46] and in contrast with the results presented by Kim and Ward [59]. In addition, Santeramo [7] concludes that, in markets of perishable products, price rises tend to be slowly transmitted and do not influence distant markets; on the contrary, shocks originated by price decreases spread across markets. The results are in line with Ward [40] who has demonstrated that the high perishability, and the inability to delay sales through temporary storage implies that decreases in wholesale prices have a larger effect on retail prices than increases.…”
Section: A Focus On Perishable Marketssupporting
confidence: 86%
“…The interest on prices dynamics in perishable markets and the number of studies focused on these topics have rapidly increased during last decades [1][2][3][4][5][6][7]: the implications for agricultural markets, for entrepreneurial strategies, and for producer and consumer welfare are relevant and worth for a deep investigation.…”
Section: Introductionmentioning
confidence: 99%
“…The Fruits and vegetables (F&Vs) sector is growing rapidly worldwide (Santeramo, 2015c;Santeramo & von Cramon-Taubadel, 2016;Pilone et al, 2017). The main reasons of the market growth are a growing consumers' interest in ready to eat food (Artés et al, 2009), and a growing demand of food with higher safety standards (James et al, 2010).…”
Section: Fruits and Vegetablesmentioning
confidence: 99%
“…Most studies have focused on short-run impacts on poverty by using pre-crisis household survey data (Jansen & Miller, 2008b;Woden et al, 2008;Robles & Torero, 2010;Wodon & Zaman, 2010;Skoufias et al, 2011;Roselli et al, 2012;Ivanic et al 2012;D'souza & Jolliffe, 2012). Although the effect of price transmission (Santeramo, 2015c) and crises differs in magnitude across countries and households, there is widespread agreement that national poverty levels have increased and that urban populations tend to be more negatively affected than their rural counterparts.…”
Section: Introductionmentioning
confidence: 99%